Hydrothermally Grown Zinc Oxide Nanostructures@Carbon Composites for Supercapacitor Application. Issue 1 (7th December 2022) - Gupta, Manish Kumar; Kumar, Yogesh; Sonnathi, Neeleshwar; Sharma, Sanjay Kumar
Abstract : A simple approach for growing porous nanostructured zinc oxide (ZnO) and making its well‐dispersed nanocomposite with activated carbon (AC) is demonstrated. Synthesis is done hydrothermally at 140 °C for 10 hours. X‐ray diffraction (XRD), energy‐dispersive X‐ray (EDX), and scanning electron microscope (SEM) measurements confirm the formation of crystalline ZnO nanoparticles with flower‐shaped morphology comprising clusters of nanopetals. ZnO and its composite with AC are used to fabricate symmetric hybrid supercapacitors. The electrochemical performance of ZnO electrode is compared to ZnO–AC composite electrode using 1 M Na2 SO4 aqueous electrolyte. The electrochemical performance evaluated by cyclic voltammetry (CV) and galvanostatic charge–discharge (GCD) demonstrates enhanced charge storage in ZnO–AC electrodes. The specific capacitance values of ZnO and ZnO–AC‐based electrodes are found to be 214 and 298 F g −1 respectively at a current density of 1 A g −1 and the energy densities are 29.72 and 48.39 Wh kg −1 respectively at power density of 1 kW kg −1 . The porous space between ZnO nanopetals and its high surface area geometry coupled with complementing properties of AC seems to facilitate a synergistic effect between ZnO's faradaic and AC's electric double‐layer charge storage mechanisms, thus leading to enhanced specific capacitance with superior performance. Abstract : Hydrothermal synthesis of zinc oxide nanoflakes mixed with activated carbon is discussed. X‐ray diffraction, energy‐dispersive X‐ray, Fourier‐transform infrared, and scanning electron microscope are used to confirm the formation of nanomaterials. Pure zinc oxide and its composite with activated carbon electrodes are shown to have specific capacitances of 214 and 298 F g −1 and energy densities 29.72 and 1348.39 Wh kg −1, respectively.